Faktor-faktor yang Memengaruhi Ekspor Udang di PT BeeJay Seafood - Azzahran, Muhammad Rafi; Ariadi, Bambang Yudi (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Indonesia is an archipelagic country with abundant fishery resources, one of the commodities is shrimp which is the main export commodity. PT BeeJay Seafood, as a seafood processing and export company in Probolinggo, faces fluctuations in shrimp exports influenced by various factors. This study aims to analyze the influence of exchange rates, inflation, shrimp prices in the domestic market, and shrimp production volume in Indonesia on the shrimp export volume of PT BeeJay Seafood. This study uses a quantitative method with a multiple linear regression approach. The data used is secondary data for the period from December 2023 to November 2024. The shrimp export trend at PT BeeJay Seafood shows a fluctuating pattern. The results of the analysis showed that partially, the rupiah exchange rate against the US dollar and inflation had a positive and significant effect, while the price of shrimp in the domestic market and the volume of shrimp production in Indonesia had no effect on shrimp exports carried out by PT BeeJay Seafood. Partially, all independent variables affect PT BeeJay Seafood's shrimp exports. This study shows that fluctuations in the rupiah exchange rate against the US dollar and inflation need to be the main concern in PT BeeJay Seafood's shrimp export strategy. In addition, companies need to consider domestic pricing policies to increase competitiveness in the international market. The results of this research are expected to provide insight for companies in optimizing shrimp exports.